A Study on the Role of Omega Fatty Acids as an Adjuvant Therapy in Treatment of Amblyopia - Shipra Sharda (Delhi Journal of Ophthalmology)
Aim: To study the role of omega fatty acids as an adjuvant therapy in treatment of amblyopia. Methods: This prospective, randomized, interventional study included thirty two patients aged 5-12 years of age with unilateral amblyopia or bilateral amblyopia. One group (A) of sixteen patients were prescribed occlusion therapy and the other group (B) received 1000 mg per day of omega fatty acids along with occlusion for a period of three months. Follow-up assessments included best corrected visual acuity (BCVA) (both distance and near) and stereoacuity measurements at 1 week and end of three months. Results: The mean age of the patients was 8.68 ± 1.55 years. The mean baseline visual acuity for distance was 0.85 ± 0.071 Log MAR equivalent for Group A and 0.81 ± 0.073 Log MAR eq for Group B. At the end of therapy, the mean visual acuity was 0.48 ± 0.91 Log MAR eq and 0.40 ± 0.20 Log MAR equivalent for Group A and B respectively. There was statistically significant improvement in vision within Group A (p value-0.0008) and Group B (p value-0.0001). When both groups were compared, the results were insignificant (p value-0.373). Conclusion: Omega fatty acids improve visual acuity in patients with amblyopia and maintain improved visual acuity but there is no additional benefit when compared to patching alone. This study encourages further research on this subject.